Antimicrobial impact of a propolis/PVA/chitosan composite and its prospective application against methicillin resistance bacterial infection - Alarjani, Khaloud Mohamed; Yehia, Hany Mohamed; Badr, Ahmed Noah; Ali, Hatem S.; Al-Masoud, Abdulrahman H.; Alhaqbani, Sarah M.; Alkhatib, Shahad A.; Rady, Ahmed M.; Abdel-Maksoud, Mostafa (Frontiers in Nanotechnology, 2024)
Seriously damaged skin could be infected by methicillin-resistant bacteria, which delays restoration. Propolis has bioactivity linked with its minor components, such as antimicrobials and antioxidants. Active sites in polyvinyl alcohol (PVA) and chitosan (CS) can enhance the nanoloading of natural extracts with activity amelioration. Korean propolis extract (KPE) loading to a nanocomposite possibly enhances its antimicrobial and anti-inflammatory potency. Composites were formed using two PVA/ CS structures (1:1; 2:1), and their skin-application appropriateness was determined by mechanical properties, moisture content, water activity, and color. The composite of PVA/CS (1:1) was more practicable for KPE-loading. Increasing KPE concentrations (50, 100, 150, and 200 ng/mL) alters composite bioactivity measured by Fourier transmission infrared (FT-IR). Antibacterial potency of 200 ng KPE/mL was the most effective concentration, followed by 150 ng KPE/mL, against Staphylococcus aureus (MRSA) and Clostridium perfringens. The composite activity was measured as minimum inhibition (MIC) and minimum bacterial concentrations (MBC). At 200 ng KPE/mL, MIC and MBC against MRSA were 14.93±1.21 and 20.21±1.97 mg composite/mL, respectively. Significant inhibition was also recorded for antibiofilm formation, where MRSA growth was not detected after four hours of time intervals to the stainless-steel coupon. Compared to planktonic bacteria, the formed barrier of PVA/CS restrained the biofilm matrix formation and supported KPE antimicrobial. The impact of inhibition against biofilm formation depends on two parallel mechanisms (PVA barrier with hydrogen bonds, besides nano-KPE particle penetration into bacterial cells). The KPE-composite application to rats' wounds shows significantly reduced MRSA infection. The results demonstrate the capability of KPE composite in reducing infection, healing correctly, and restoring hair. The wound swabbed test emphasizes this capacity, in which bacterial growth rate restriction was evaluated using a plate count assay. The results recommended 150 ng KPE/mL loading into CS/PVA (1:1) as an effective anti-pathogenic treatment, particularly against the MRSA infection of wounds.